Estudo de biocombatibilidade de uma nova membrana de látex associada ao óxido nítrico e de sua influência na reparação óssea - Tzu, Lee Chen (2011)
Bone regeneration of lesions with large magnitude remains a challenge for science. So, the search for new materials that can aid bone healing is still an importante research topic. This work consists of the study of in vivo biocompatibility of a new látex membrane that gradually releases nitric oxide (NO): Latex DETC-NO-Fe (iron diethyldimethylcarbamate) and its influence on the repair of bone defects, literature indicates that NO can contribute in the process of healing. The in vivo biocompatibility was performed by means of subcutaneous implantation in the dorsum of rats, comparing the response produced by natural latex, latex industry, polytetrafluethylene membrane (PTFE). The experiment of bone regeneration was performed on the skull of rabbits, covering defects of 5mm by Latex, Latex DETC-Fe-NO and PTFE membranes. The tissue reaction, compared to subcutaneous implantation of the materials was evaluated microscopically by counting inflammatory cells and the thickness of the fibrous capsule 7, 14 and 35 days post surgery. The results indicate, , a reduction of mononuclear inflammatory cells and an increased thickness of the fibrous capsule (P <0.05) over the period of analysis. The histomorphometry of bone tissue in the defect region, performed 7, 15 and 30 days after surgery, shows a greater tissue formation in bone defects covered with the latex Fe-DETC-NO membrane (P <0.05) 30 days after surgery . Immunohistochemical analysis against Osteocalcin, Osteopontin, tartrate-resistant acid phosphatase (TRAP), Vascular Endothelial growth factor (VEGF), were made to access osteoblastic cell lineage, extracellular matrix, osteoclasts and blood vessels in the defect region. The immunolabeling for VEGF in the central region at 7 days for samples treated by Latex Fe-DETC-NO indicate greater angiogenic activity, which may be associated with increased bone formation observed at 30 days.